2007
DOI: 10.1021/ef060422f
|View full text |Cite
|
Sign up to set email alerts
|

High Heat Sink Jet Fuels. 2. Stabilization of a JP-8 with Model Refined Chemical Oil/Light Cycle Oil (RCO/LCO)-Derived Stabilizers

Abstract: JP-900 is the generic name given to a future jet fuel that will be required to handle an anticipated thermal stress of ∼900 °F (482 °C) for several hours. We report flowing rig scouting results, under approximate JP-900 conditions, examining the effect on both oxidative and pyrolytic stability of the addition of a few volume percent of model refined chemical oil/light cycle oil (RCO/LCO)-derived compounds to a petroleum-derived JP-8. Tetralin, tetralone, and tetralol were used as model hydroaromatic compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
(32 reference statements)
2
17
0
Order By: Relevance
“…The experiment was performed at 655 °C and 37 bar pressure with a feed flow rate of 2.9 mL/min. It is reported that the coke formation reduced significantly (more than 13 times) in the presence of 300 ppm of diphenyl selenide in the fuel and for a test duration of 12 h. Sobkowiak et al have investigated the influence of tetralin and tetralone mixture as an additive on the coke propensity of JP-8 fuel under supercritical conditions. The study was carried out in a silica-coated tubular reactor at 675 °C and 38 bar pressure with a feed flow rate of 2.2 mL/min.…”
Section: Phenomena Of Coking During the Thermal Degradation Of Hydroc...mentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment was performed at 655 °C and 37 bar pressure with a feed flow rate of 2.9 mL/min. It is reported that the coke formation reduced significantly (more than 13 times) in the presence of 300 ppm of diphenyl selenide in the fuel and for a test duration of 12 h. Sobkowiak et al have investigated the influence of tetralin and tetralone mixture as an additive on the coke propensity of JP-8 fuel under supercritical conditions. The study was carried out in a silica-coated tubular reactor at 675 °C and 38 bar pressure with a feed flow rate of 2.2 mL/min.…”
Section: Phenomena Of Coking During the Thermal Degradation Of Hydroc...mentioning
confidence: 99%
“…To simulate the actual scenario in a laboratory, different approaches were adopted by various researchers in designing the test rig for the experimental investigation. Some groups of scientists have used direct heating DC power systems (as shown in Figure a) to heat the reactor to the desired temperature. ,, The other groups ,, have used furnace heating systems as shown in Figure b. We believe that the furnace heating approach is justifiable if the objective is to estimate the fuel conversion and coking rate.…”
Section: Comparison Of Laboratory Test Setup Adopted For Endothermic ...mentioning
confidence: 99%
“…It has been proved that 1,2,3,4-tetrahydronaphthalene can significantly delay the formation of carbonaceous materials in hydrocarbon fuels as a hydrogen donor. 14 Because adding 1,2,3,4-tetrahydronaphthalene and n-decane to exo-tetrahydrodicyclopentadiene can improve the thermal stability of exo-tetrahydrodicyclopentadiene and its fluidity, it is vital to study the properties of the ternary system and the three corresponding binary systems. There have also been many reports on n-decane and 1,2,3,4-tetrahydronaphthalene mixtures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The temperature of the hydrocarbon fuel is higher than the cracking temperature of the carbon–carbon bond when the aircraft cruises at a hypersonic speed, which may lead to some safety problems such as carbon deposition and blockage of pipelines. It has been proved that 1,2,3,4-tetrahydronaphthalene can significantly delay the formation of carbonaceous materials in hydrocarbon fuels as a hydrogen donor …”
Section: Introductionmentioning
confidence: 99%
“…A promising approach to enhance the thermal stability of fuel is the use of thermal stabilizers. Many previous studies on thermal stabilizers have focused on hydrogen donors (H donors), such as 1,2,3,4-tetrahydroquinoline (THQ), benzyl alcohol (BnOH), and tetralin (THN). H donors terminate the propagation of radicals produced upon thermal decomposition of fuel.…”
Section: Introductionmentioning
confidence: 99%